Praktik Jual Beli Kotoran Hewan Dalam Perspektif Mazhab Imam Syafi’i : (Studi Kasus Di PT. Leong Ayam 1 Primadona Desa Serapuh ABC Kec. Padang Tualang Kab. Langkat) - Sri Wahyuni, Abdullah Sani, Diyan Yusri (Mediation : Journal Of Law, 2022)
Legal Practice of Buying and Selling Animal Impurities According to Imam Syafi'i School (Case Study in Serapuh ABC Village, Padang Tualang District). This research is included in the qualitative research model, meaning that the data used in this study is qualitative data (data that does not consist of numbers) in the form of verbal dialogue messages and writings that become the results of research through observation, interviews and documentation. In the case of divorce the most disadvantaged are the wife who in particular does not have her own income and her own place of residence. The formulation of this research is 1. How is the practice of buying and selling animal dung in Serapuh ABC Village, Kec. Padang Tualang? .2. How is the legal analysis of buying and selling animal waste in accordance with the hadith and the related meaning of the hadith? 3. What is the legal practice of buying and selling animal dung according to Imam Shafi'i ?. The results of this study are: 1. Based on the practice of buying and selling animal droppings in the village of Serapuh ABC, Padang Tualang district, Langkat regency Sales of animal droppings are common among the people and are in accordance with the principles of the Shari'a and the rules of buying and selling. Starting from the pillars of buying and selling terms, goods and so forth so that buying and selling animal dung in the village of Serapuh ABC, Padang Tualang district, Langkat regency according to religion may be carried out and not violate religious norms. 2. Based on the perspective of Istihsan Islamic Law on the Sale and Purchase of animal dung according to unclean goods, it is prohibited by religion. In the development of customs that will require the need for manure as additional fertilizer for plantations and agriculture, the sale and purchase of animal manure is legally permissible, because of the benefits. Even though the Imams of Madhzab differ, but with animal manure to be used as manure, so it can be said that it can be done for buying and selling transactions.